2004
DOI: 10.1063/1.1787165
|View full text |Cite
|
Sign up to set email alerts
|

High-performance magnetic field sensor based on superconducting quantum interference filters

Abstract: We have developed an absolute magnetic field sensor using Superconducting Quantum Interference Filter (SQIF) made of high-Tc grain boundary Josephson junctions. The device shows the typical magnetic field dependent voltage response V (B), which is sharp delta-like dip in the vicinity of zero magnetic field. When the SQIF is cooled with magnetic shield, and then the shield is removed, the presence of the ambient magnetic field induces a shift of the dip position from B0 ≈ 0 to a value B ≈ B1, which is about the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…The two states are fully reversible: we can move from the first state (magnetic shield on, dip positioned at ), to the second state (magnetic shield off, dip positioned at ), and vice versa, by slowly removing/replacing the magnetic shield. Opposite to previous experiments [12], the dip amplitude is almost unaffected in nonshielded conditions, and also the side modulations are only slightly perturbed by the ambient magnetic field. As long as we do not perform a new thermal cycle through , the two states are reproducible within the accuracy of our experimental set-up ( 1%).…”
Section: A the Curvessupporting
confidence: 58%
See 1 more Smart Citation
“…The two states are fully reversible: we can move from the first state (magnetic shield on, dip positioned at ), to the second state (magnetic shield off, dip positioned at ), and vice versa, by slowly removing/replacing the magnetic shield. Opposite to previous experiments [12], the dip amplitude is almost unaffected in nonshielded conditions, and also the side modulations are only slightly perturbed by the ambient magnetic field. As long as we do not perform a new thermal cycle through , the two states are reproducible within the accuracy of our experimental set-up ( 1%).…”
Section: A the Curvessupporting
confidence: 58%
“…Our recent experiments have shown that SQIFs might serve as absolute sensors of the Earth magnetic field [12]. In this contribution, we present an experiment with one dimensional (1D) SQIF magnetometers surrounded by an on-chip superconducting pick-up loop, which has enhanced the magnetic field sensitivity of about 10 times with respect to the bare SQIF of the same geometry except the pick-up loop.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of flux coupled into the array due to B E is also difficult to estimate considering the well-known large flux focusing effects in bicrystal Josephson junctions. 41,42 For these reasons, here we restrict ourselves with only a qualitative comparison between the model and the experimental data and this indicates good agreement between them.…”
Section: Fig 5 (A) G(%)mentioning
confidence: 99%
“…3). Such B-tunability can find application in electronic devices based on multiple JJs such as rapid single flux quantum (RSFQ), 40 SQUIDs, 41 or superconducting quantum interference filters (SQIFs) 42,43 when a tunable preferential direction of flux flow is required. In order to qualitatively understand why efficiency changes sign when B is varied, it is important to understand that usually, during the device's operation, there are many U 0 per array loop involved in the ratchet's dynamics.…”
mentioning
confidence: 99%
“…4,8,9 Active cooling offers numerous advantages: possibility to choose stable temperature down to 50 K, quick thermal cycles, and compact and portable setups. 10 Results obtained in unshielded microcoolers have never revealed a significant degradation of the SQIF-sensor performance with respect to shielded microcoolers.…”
mentioning
confidence: 99%